Analisis Peran Pemerintah Dalam Ketersediaan Barang Publik - Sarah Bakara; Maya Wulandari; Eliza Handayani Lubis; Armin Rahmansyah Nasution; Juanda Maulana; Siti Naila Rahmi; Jelita Simanungkalit (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This article aims to analyze the role of the government in providing public goods as a form of service to the community. The government has a crucial role in the provision of public goods, which includes the functions of allocation, distribution, and stabilization. In this context, public goods are defined as goods that can be enjoyed by everyone without reducing their availability to others (non-rivalrous and non-excludable). In accordance with the purpose of this study, which is to find out the role of the government in the availability of public goods. The type of data used in this study is secondary data, secondary data according to Sugiyono (2016:225) is a source of data that does not directly provide data to data collectors, for example through other people or through documents. And those that become secondary sources of data are books, articles, journals related to research.